2013
DOI: 10.1093/bioinformatics/btt647
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of expanded short tandem repeats in personal genomics using hybrid sequencing

Abstract: Motivation: Long expansions of short tandem repeats (STRs), i.e. DNA repeats of 2–6 nt, are associated with some genetic diseases. Cost-efficient high-throughput sequencing can quickly produce billions of short reads that would be useful for uncovering disease-associated STRs. However, enumerating STRs in short reads remains largely unexplored because of the difficulty in elucidating STRs much longer than 100 bp, the typical length of short reads.Results: We propose ab initio procedures for sensing and locatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…Furthermore, many sequencing technologies have a limited ability to genotype some 385 tandem repeat variants [27,[41][42][43][44], so our results apply to any data that is limited to…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many sequencing technologies have a limited ability to genotype some 385 tandem repeat variants [27,[41][42][43][44], so our results apply to any data that is limited to…”
mentioning
confidence: 99%
“…Recent advances in sequencing technology [42,43,45] and tandem repeat 387 genotyping [6,44,46,47] provide hope that some hypermutable elements will be included 388 in future studies of genetic heritability and genetic disease. Nevertheless, some of the often caused by expansion [14,18].…”
mentioning
confidence: 99%
“…The recent development of single-molecule sequencing platform produces reads that are sufficiently long to span the entire gene or small viral genome. It not only benefits the assembly of genomic regions with tendem repeat [23][24][25], but also offers the opportunity to examine the genetic linkage between mutations. In fact, it is shown that the long read in single-molecule sequencing aids haplotype phasing in diploid genome [26], and in polyploid genome [27].…”
Section: Discussionmentioning
confidence: 99%
“…This error rate might not be acceptable for individuals at the edge of one of the repeat ranges. In the future, HD genetic testing might require a two-tier approach using an additional long-read sequencing platform such as PacBio [34, 35] for persons with CAG lengths in the equivocal ranges (i.e., within 2 CAG repeats of another range).…”
Section: Discussionmentioning
confidence: 99%